Composition, electrolytic solution, polymer electrolyte, electrochemical device, and fluoropolyether

JP2025036336AActive Publication Date: 2025-03-14DAIKIN INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024147455
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-29
Publication Date
2025-03-14
Estimated Expiration
2044-08-29

AI Technical Summary

Benefits of technology

【0023】 本開示によれば、電気化学デバイスの高温耐久性を改善できる組成物、電解液、ポリマー電解質、電気化学デバイス、及び、フルオロポリエーテルを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036336000001
    Figure 2025036336000001
  • Figure 2025036336000002
    Figure 2025036336000002
  • Figure 2025036336000003
    Figure 2025036336000003
Patent Text Reader

Abstract

To provide a composition, an electrolytic solution, a polymer electrolyte, an electrochemical device, and fluoropolyether which can improve high temperature durability of an electrochemical device.SOLUTION: A composition contains at least one of fluoropolyether represented by any one of the following formulae (1) to (3), and a salt. Formula (1): R1-O-Ra1-Rb1-O-Ra1-R1, Formula (2): R2-Rb2-O-Ra2-Rb2-R2, and Formula (3): R3-Rb3-O-Ra3-R3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to compositions, electrolytes, polymer electrolytes, electrochemical devices, and fluoropolyethers. [Background technology]

[0002] 2. Description of the Related Art With the trend toward lighter and smaller electric appliances in recent years, the development of electrochemical devices having high energy density, such as lithium ion secondary batteries, has progressed.

[0003] As a technique relating to electrochemical devices, Patent Document 1 discloses a liquid composition containing a specific (per)fluoropolyether. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2019-523529 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide a composition, an electrolyte, a polymer electrolyte, an electrochemical device, and a fluoropolyether that can improve the high-temperature durability of an electrochemical device. [Means for solving the problem]

[0006] The present disclosure (1) is a composition containing at least one fluoropolyether represented by any one of the following formulas (1) to (3) and a salt. (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R 2 -Rb 2 -O-Ra 2 -Rb2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (In the formula, Ra 1 ~Ra 3 are each independently a polyoxyalkylene group containing 4 to 50 oxyalkylene units not containing fluorine, Ra 1 ~Ra 3 each oxyalkylene unit is independently -CHCHO- or -CHCH(J)O-; Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 3 are each independently a fluoropolyether group represented by the following formula (4): R 1 and R 3 each independently represents a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 2 are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0007] The present disclosure (2) relates to the Ra 1 ~Ra 3 are each independently a polyoxyalkylene group represented by the following formula (Ra-I): (Ra-I): -(CH2CH2O)r(CH2CH(CH3)O)s(CH2CH(CH2CH3)O)t(CH2CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

[0008] This disclosure (3) relates to the Ra 1 ~Ra 3 The composition according to the present disclosure (1) or (2), wherein the number average molecular weight is 40 to 4,000.

[0009] The present disclosure (4) is the composition according to any one of the present disclosures (1) to (3), in which the Rfs are each independently a fluoropolyether group represented by the following formula (Rf-I): Formula (Rf-I): -(OC6F 12 )a-(OC5F 10 )b-(OC4F8)c-(OC3Rc6)d-(OC2F4)e-(OCF2)f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeat unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e, and f is 1 or greater.

[0010] The present disclosure (5) is the composition according to any one of the present disclosures (1) to (4), in which the Rfs are each independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): Formula (Rf-II): -(OC3F6)d-(OC2F4)e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary.

[0011] This disclosure (6) relates to the R 1 ~R 3 is the composition according to any one of the present disclosures (1) to (5), wherein each of the is independently a methyl group, an ethyl group, a trifluoromethyl group, or a pentafluoroethyl group.

[0012] The present disclosure (7) is the composition according to any one of the present disclosures (1) to (6), wherein the salt is a lithium salt.

[0013] The present disclosure (8) is the composition according to any one of the present disclosures (1) to (7), wherein the content of the salt is 0.1 to 30 mass %.

[0014] The present disclosure (9) is the composition according to any one of the present disclosures (1) to (8), which is liquid at any temperature between 25°C and 80°C.

[0015] The present disclosure (10) is the composition according to any one of the present disclosures (1) to (9), in which the content of the polyalkylene oxide represented by the following formula (5) is less than 20 mass %. (5)R 1B -(OCHR 1A (CH2)jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is an integer of 0 or 1 to 2, R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

[0016] The present disclosure (11) is an electrolyte solution containing the composition according to any one of the present disclosures (1) to (10).

[0017] The present disclosure (12) is a method for producing a ferroelectric liquid having an ionic conductivity of 1.0×10 -7 ~1.0×10 -3 The electrolyte solution according to the present disclosure (11) has a viscosity of 1.0 S / cm.

[0018] The present disclosure (13) is the electrolyte solution according to the present disclosure (11) or (12), in which the Li-ion transport number is 0.2 to 0.5.

[0019] The present disclosure (14) is a polymer electrolyte containing the electrolytic solution according to any one of the present disclosures (11) to (13).

[0020] The present disclosure (15) is an electrochemical device comprising the electrolyte solution according to any one of the present disclosures (11) to (13) or the polymer electrolyte according to the present disclosure (14).

[0021] The present disclosure (16) is a fluoropolyether represented by the following formula (2A). (2A)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (In the formula, Ra 2 is a polyoxyalkylene containing 4 to 50 oxyalkylene units not containing fluorine, Ra 2 each oxyalkylene unit is independently -CHCHO- or -CHCH(J)O-; Each J is independently an alkyl group or an aryl group; Rb 2 are each independently a fluoropolyether group represented by the following formula (4A): R 2are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4A)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0022] The present disclosure (17) relates to the Ra 2 is a polyoxyalkylene group represented by the following formula (Ra-I), and each Rf is independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II), in the fluoropolyether according to the present disclosure (16). (Ra-I): -(CH2CH2O)r-(CH2CH(CH3)O)s-(CH2CH(CH2CH3)O)t-(CH2CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.) Formula (Rf-II): -(OC3F6)d-(OC2F4)e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary. Effect of the Invention

[0023] According to the present disclosure, it is possible to provide a composition, an electrolyte, a polymer electrolyte, an electrochemical device, and a fluoropolyether that can improve the high-temperature durability of an electrochemical device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present disclosure will now be described in detail.

[0025] <Composition> The present disclosure relates to a composition containing at least one fluoropolyether represented by any one of the following formulas (1) to (3) and a salt. (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (In the formula, Ra 1 ~Ra 3 are each independently a polyoxyalkylene group containing 4 to 50 oxyalkylene units not containing fluorine, Ra 1 ~Ra 3 each oxyalkylene unit is independently -CHCHO- or -CHCH(J)O-; Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 3 are each independently a fluoropolyether group represented by the following formula (4): R 1 and R 3 each independently represents a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 2are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0026] Since the composition of the present disclosure has the above-mentioned configuration, it is possible to improve the high-temperature durability (particularly the cycle performance at high temperatures) of an electrochemical device.

[0027] In addition, while conventional electrolyte solutions tend to be highly flammable, the composition of the present disclosure is flame retardant and has higher electrochemical stability than conventional electrolyte solutions, which can improve the ease of handling of electrochemical devices. Furthermore, the composition also has good ionic conductivity and transport number.

[0028] In addition, fluoropolyethers usually have low solubility for salts and therefore do not have sufficient ionic conductivity, making it difficult to use them as a solvent for an electrolyte solution. However, the fluoropolyethers represented by any of the above formulas (1) to (3) can dissolve salts and have sufficient ionic conductivity, and therefore can be used as a solvent for an electrolyte solution.

[0029] Ra 1 ~Ra 3 When the oxyalkylene unit is -CHCH(J)O-, the alkyl group of J may be linear or branched, but is preferably linear. The number of carbon atoms in the alkyl group of J is preferably 1 to 3. Examples of the aryl group represented by J include a phenyl group, a 4-nitrophenyl group, a 4-acetylaminophenyl group, and a 4-methanesulfonylphenyl group.

[0030] Ra 1 ~Ra 3are preferably each independently a polyoxyalkylene group represented by the following formula (Ra-I). (Ra-I): -(CH2CH2O)r-(CH2CH(CH3)O)s-(CH2CH(CH2CH3)O)t-(CH2CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

[0031] In the above formula (Ra-I), r is preferably 1 or more, more preferably 2 or more, and is preferably 30 or less, more preferably 20 or less. s, t and u are preferably 10 or less, more preferably 5 or less, and further preferably 0. r+s+t+u is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.

[0032] Ra 1 ~Ra 3 The number average molecular weight of is preferably 40 or more, more preferably 100 or more, and is preferably 4000 or less, more preferably 1000 or less. In the present specification, Ra 1 ~Ra 3 The number average molecular weight of 1 This is a value measured by H-NMR.

[0033] Rb 1 ~Rb 3 In the above formula (4), Rf 1 and Rf 2 The alkylene group may be linear or branched, but is preferably linear. Rf 1 and Rf 2 The alkylene group is preferably a fluorine-substituted alkylene group substituted with a fluorine atom. Rf 1 and Rf 2 The alkylene group preferably has 1 to 3 carbon atoms.

[0034] Rb 1 ~Rb 3 In the above formula (4), Rf may have a ring structure.

[0035] Rb 1 ~Rb 3 In the above formula (4), Rf is preferably a fluoropolyether group represented by the following formula (Rf-I). Formula (Rf-I): -(OC6F 12 )a-(OC5F 10 )b-(OC4F8)c-(OC3Rc6)d-(OC2F4)e-(OCF2)f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeat unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e, and f is 1 or greater.

[0036] Rc is preferably a hydrogen atom or a fluorine atom, and more preferably a fluorine atom, That is, Rf in the formula (4) is preferably a perfluoropolyether group.

[0037] It is preferable that a, b, c, d, e and f each independently represent an integer of 0 to 100.

[0038] The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, and may be 15 or more or 20 or more. The sum of a, b, c, d, e and f is preferably 100 or less, more preferably 60 or less, and may be 50 or less or 30 or less.

[0039] Each repeat unit denoted by a, b, c, d, e, or f may be linear or branched. -(OC6F 12 )- may be, for example, any of -(OCF2CF2CF2CF2CF2CF2)-, -(OCF(CF3)CF2CF2CF2CF2)-, -(OCF2CF(CF3)CF2CF2CF2)-, -(OCF2CF2CF(CF3)CF2CF2)-, -(OCF2CF2CF2CF(CF3)CF2)-, or -(OCF2CF2CF2CF2CF(CF3))-. -(OC5F 10 )- may be, for example, any of -(OCF2CF2CF2CF2CF2)-, -(OCF(CF3)CF2CF2CF2)-, -(OCF2CF(CF3)CF2CF2)-, -(OCF2CF2CF(CF3)CF2)-, or -(OCF2CF2CF2CF(CF3))-. -(OC4F8)- may be, for example, any of -(OCF2CF2CF2CF2)-, -(OCF(CF3)CF2CF2)-, -(OCF2CF(CF3)CF2)-, -(OCF2CF2CF(CF3))-, -(OC(CF3)2CF2)-, -(OCF2C(CF3)2)-, -(OCF(CF3)CF(CF3))-, -(OCF(C2F5)CF2)-, or -(OCF2CF(C2F5))-. -(OC3F6)- (that is, in the above formula (Rf-I) where all Rc are fluorine atoms) may be, for example, any of -(OCF2CF2CF2)-, -(OCF(CF3)CF2)-, and -(OCF2CF(CF3))-. -(OC2F4)- may be, for example, -(OCF2CF2)- or -(OCF(CF3))-.

[0040] Rf may be a group represented by any one of the following formulas (Rf-II) to (Rf-IV). Formula (Rf-II): -(OC3F6)d-(OC2F4)e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary. Formula (Rf-I-III): -(R 20 -R 21 )g- (In the formula, R 20 is OCF2 or OC2F4, R 21 are OC2F4, OC3F6, OC4F8, OC5F 10 and OC6F 12 or a combination of two or three groups selected from these groups, g is an integer from 2 to 100. Formula (Rf-I-IV): -(OC6F 12 )a-(OC5F 10 )b-(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, e is an integer of 1 to 200, a, b, c, d, and f each independently represent an integer of 0 to 200; The order of each repeating unit with a, b, c, d, e, or f is arbitrary. Formula (Rf-IV): -(OC6F 12 )a-(OC5F 10 )b-(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, f is an integer of 1 to 200, a, b, c, d, and e each independently represent an integer of 0 to 200; The order of each repeating unit with a, b, c, d, e, or f is arbitrary.

[0041] In the above formula (Rf-II), d is preferably 5 to 200, more preferably 10 to 100, and further preferably 15 to 50, and may be 25 to 35. The above formula (Rf-II) is preferably a group represented by -(OCF2CF2CF2)d- or -(OCF(CF3)CF2)d-.

[0042] In the above formula (Rf-I-II), e and f are each independently an integer of preferably 5 to 200, more preferably 10 to 200. The sum of c, d, e and f is preferably 5 or more, more preferably 10 or more, and may be 15 or more, or 20 or more. The above formula (Rf-I-II) is preferably a group represented by -(OCF2CF2CF2CF2)c-(OCF2CF2CF2)d-(OCF2CF2)e-(OCF2)f- or a group represented by -(OC2F4)e-(OCF2)f-, and more preferably a group represented by -(OC2F4)e-(OCF2)f-.

[0043] In the above formula (Rf-I-III), R 20 is preferably OC2F4, and R 21is preferably a group selected from OC2F4, OC3F6 and OC4F8, or a combination of two or three groups independently selected from these groups, and more preferably a group selected from OC3F6 and OC4F8. The combination of two or three groups independently selected from OC2F4, OC3F6 and OC4F8 is not particularly limited, and examples thereof include -OC2F4OC3F6-, -OC2F4OC4F8-, -OC3F6OC2F4-, -OC3F6OC3F6-, -OC3F6OC4F8-, -OC4F8OC4F8-, -OC4F8OC3F6-, -OC4F8OC2F4-, -OC Examples include 2F4OC2F4OC3F6-, -OC2F4OC2F4OC4F8-, -OC2F4OC3F6OC2F4-, -OC2F4OC3F6OC3F6-, -OC2F4OC4F8OC2F4-, -OC3F6OC2F4OC2F4-, -OC3F6OC2F4OC3F6-, -OC3F6OC3F6OC2F4-, and -OC4F8OC2F4OC2F4-. In the above formula (Rf-I-III), g is preferably an integer of 3 or more, more preferably an integer of 5 or more. The above g is preferably an integer of 50 or less. In the above formula (Rf-I-III), OC2F4, OC3F6, OC4F8, OC5F 10 , and OC6F 12 may be either linear or branched, and is preferably linear. In this embodiment, the above formula (Rf-I-III) is preferably -(OC2F4-OC3F6)g- or -(OC2F4-OC4F8)g-.

[0044] In the above formula (Rf-I-IV), e is preferably an integer of 1 to 100, more preferably an integer of 5 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example, 10 to 100.

[0045] In the above formula (Rf-IV), f is preferably an integer of 1 to 100, more preferably an integer of 5 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example, 10 to 100.

[0046] In Rf, the ratio of e to f (hereinafter referred to as "e / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the e / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the e / f ratio, the more the lubricity is improved. On the other hand, by making the e / f ratio 0.5 or more, the stability of the compound can be further improved. The larger the e / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of the e / f ratio is preferably 0.8 or more.

[0047] Rf is represented by the following formula (Rf-I-VI): -(OCF2CF2CF2)a-(OCF(CF3)CF2)b-(OCF2CF(CF3))c-(OCF2CF2)d-(OCF(CF3))e-(OCF2)f- (In the formula, a, b, c, d, e, and f each independently represent an integer of 0 to 200, the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeating unit with a, b, c, d, e, or f is arbitrary. The group may be represented by the following formula:

[0048] Rf is represented by the following formula (Rf-I-VII): -(OCF2CF2)d-(OCF(CF3))e-(OCF2)f- (In the formula, d, e, and f each independently represent an integer of 0 to 200, the sum of d, e, and f is 1 or more, The order of the repeating units marked with d, e, or f is arbitrary. When Rf is this group, it is considered that the salt solubility becomes better because the number of ether bonds increases and the cations of the salt become more easily coordinated.

[0049] In Rf, the ratio of d to f (hereinafter referred to as "d / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the d / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the d / f ratio, the more the lubricity is improved. On the other hand, by making the d / f ratio 0.5 or more, the stability of the compound can be further improved. The larger the d / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of the d / f ratio is preferably 0.8 or more.

[0050] Each Rf is preferably independently a group represented by the above formula (Rf-II) or (Rf-I-II), and more preferably a group represented by the above formula (Rf-I-II).

[0051] The number average molecular weight of Rf is not particularly limited, but is, for example, 500 to 30,000, preferably 1,500 to 30,000, and more preferably 2,000 to 10,000. In this specification, the number average molecular weight of Rf is 19 This is a value measured by F-NMR.

[0052] R 1 ~R 3 The alkyl group and the fluoroalkyl group may be linear or branched, but are preferably linear. R 1 ~R 3 Examples of the aryl group include a phenyl group, a 4-nitrophenyl group, a 4-acetylaminophenyl group, and a 4-methanesulfonylphenyl group.

[0053] R 1 ~R 3are each independently preferably an alkyl group having 1 to 3 carbon atoms or a fluoroalkyl group having 1 to 3 carbon atoms, more preferably a methyl group, an ethyl group, a trifluoromethyl group or a pentafluoroethyl group, and further preferably a methyl group, a trifluoromethyl group or a pentafluoroethyl group.

[0054] The fluoropolyether is particularly preferably the above formula (1) because it has sufficient ion conductivity and good effects of improving high-temperature durability.

[0055] The above fluoropolyether is preferably liquid at any temperature between 25°C and 80°C, and more preferably liquid at 25°C, in view of the satisfactory effect of improving sufficient ionic conductivity and high-temperature durability. Examples of a form that is "liquid at any temperature between 25°C and 80°C" include a form that is solid at 25°C and liquid at 50°C, and a form that is solid at 50°C and liquid at 80°C. A form that is liquid at low temperatures and solid at high temperatures does not usually exist, and therefore is not included in the form that is "liquid at any temperature between 25°C and 80°C".

[0056] In the composition of the present disclosure, the content of the fluoropolyether is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. The upper limit is not particularly limited, but is usually 99.9% by mass or less, preferably 99.5% by mass or less, and more preferably 98.5% by mass or less.

[0057] As the salt, it is preferable to use any electrolyte salt that can be used in various types of battery electrolytes, such as lithium salts, sodium salts, ammonium salts, metal salts, liquid salts (ionic liquids), inorganic polymer salts, and organic polymer salts.

[0058] Batteries using the composition of the present disclosure as an electrolyte include lithium ion batteries, sodium ion batteries, magnesium ion batteries, calcium ion batteries, and fluoride ion batteries, with lithium ion batteries being preferred.

[0059] When the composition of the present disclosure is used as an electrolyte for a lithium ion battery, the electrolyte salt is preferably a lithium salt. Any lithium salt can be used as the lithium salt, and specific examples include the following: LiPF6, LiBF4, LiClO4, LiAlF4, LiSbF6, LiTaF6, LiWF7, LiAsF6, LiAlCl4, LiI, LiBr, LiCl, LiB 10 Cl 10 Inorganic lithium salts such as Li2SiF6, Li2PFO3, and LiPO2F2; Lithium tungstates such as LiWOF5; Lithium carboxylates such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, and CF3CF2CF2CF2CO2Li; Lithium salts having an S=O group, such as FSO3Li, CH3SO3Li, CH2FSO3Li, CHF2SO3Li, CF3SO3Li, CF3CF2SO3Li, CF3CF2CF2SO3Li, CF3CF2CF2CF2SO3Li, lithium methyl sulfate, lithium ethyl sulfate (C2H5OSO3Li), and lithium 2,2,2-trifluoroethyl sulfate; Lithium imide salts such as lithium bis(trifluoromethanesulfonimide) (LiTFSI), lithium bis(monofluorosulfonimide) (LiFSI), LiN(FCO)2, LiN(FCO)(FSO2), LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium bisperfluoroethanesulfonylimide, lithium cyclic 1,2-perfluoroethanedisulfonylimide, lithium cyclic 1,3-perfluoropropanedisulfonylimide, lithium cyclic 1,2-ethanedisulfonylimide, lithium cyclic 1,3-propanedisulfonylimide, lithium cyclic 1,4-perfluorobutanedisulfonylimide, LiN(CF3SO2)(FSO2), LiN(CF3SO2)(C3F7SO2), LiN(CF3SO2)(C4F9SO2), and LiN(POF2)2; Lithium methide salts such as LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3; Others, Formula: LiPF a (C n F 2n+1 ) 6-a (wherein a is an integer of 0 to 5, and n is an integer of 1 to 6) (e.g., fluorine-containing organic lithium salts such as LiPF3(C2F5)3, LiPF3(CF3)3, LiPF3(iso-C3F7)3, LiPF5(iso-C3F7), LiPF4(CF3)2, LiPF4(C2F5)2), LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, and LiBF2(C2F5SO2)2, LiSCN, LiB(CN)4, LiB(C6H5)4, Li2(C2O4), LiP(C2O4)3, Li2B 12 F b H 12-b (b is an integer of 0 to 3), etc.

[0060] Among these, LiTFSI, LiFSI, LiPF6, LiBF4, LiSbF6, LiTaF6, LiPO2F2, FSO3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethane disulfonylimide, lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, etc. are preferred, with LiTFSI, LiFSI, and LiPF6 being particularly preferred.

[0061] These lithium salts may be used alone or in combination of two or more. A preferred example of a combination of two or more is a combination of LiPF6 and LiTFSI, or a combination of LiTFSI and LiPO2F2, LiBF4, or FSO3Li, which has the effect of improving high-temperature storage characteristics, load characteristics, and cycle characteristics.

[0062] Another example is the combined use of an inorganic lithium salt and an organic lithium salt, which has the effect of suppressing deterioration due to high-temperature storage. As the organic lithium salt, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethane disulfonylimide, lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, etc. are preferred.

[0063] When the composition of the present disclosure is used as an electrolyte for a fluoride ion battery, the electrolyte salt is preferably a fluoride salt.

[0064] The above-mentioned fluoride salt is not particularly limited as long as it generates fluoride ions, and may be an organic fluoride salt or an inorganic fluoride salt. The fluoride salt may be an ionic liquid. More specifically, ammonium fluoride, metal fluoride, etc. may be used. These may be used alone or in combination of two or more. Ammonium fluoride is preferred because of its good solubility.

[0065] Specific examples of the metal fluorides include alkali or alkaline earth fluorides (e.g., LiF, CsF, MgF2, BaF2), transition metal fluorides (e.g., VF4, FeF3, MoF6, PdF2, AgF), main group metal fluorides (e.g., AlF3, PbF4, BiF3), and lanthanide or actinide fluorides (e.g., LaF3, YbF3, UF5).

[0066] Examples of the ammonium fluoride include ammonium hydrogen fluoride, alkyl ammonium fluoride, etc. From the viewpoint of good solubility, alkyl ammonium fluoride is preferred.

[0067] The above alkyl ammonium fluorides are + It is preferable that the cation represented by -Rx4 is included. Each Rx is independently an alkyl group or a fluoroalkyl group, and an alkyl group is preferable. The number of carbon atoms in Rx is, for example, 1 to 10, and may be 5 or less, or 3 or less.

[0068] The alkyl group and fluoroalkyl group in the alkyl ammonium fluoride may be straight-chain or branched-chain, but it is preferable that at least one of them is branched-chain, and it is more preferable that they contain both branched-chain and straight-chain. The alkyl group and the fluoroalkyl group preferably have 1 or more carbon atoms, and preferably 10 or less, more preferably 8 or less, and further preferably 6 or less. The linear alkyl group and linear fluoroalkyl group each preferably have 1 or more carbon atoms, and preferably 10 or less, more preferably 5 or less, and further preferably 3 or less. The branched alkyl group and branched fluoroalkyl group each preferably have 1 or more, more preferably 3 or more, and even more preferably 4 or more carbon atoms, and preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.

[0069] In the composition of the present disclosure, the content of the above salt is preferably 0.1% by mass or more, more preferably 1% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less.

[0070] In the composition of the present disclosure, the content of the polyalkylene oxide represented by the following formula (5) is preferably less than 20 mass %, which improves the chemical stability, represented by the oxidation resistance, of the composition. (5)R 1B -(OCHR 1A (CH2)jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is an integer of 0 or 1 to 2, R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

[0071] In the composition of the present disclosure, the content of the polyalkylene oxide represented by the above formula (5) is more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 1% by mass or less. The lower limit is not particularly limited, and may be 0% by mass.

[0072] <Electrolyte> The compositions of the present disclosure are useful as electrolytes since they can improve the high-temperature durability of electrochemical devices. The present disclosure also relates to an electrolyte comprising the composition of the present disclosure.

[0073] In the electrolyte solution of the present disclosure, the suitable ranges of the content of the fluoropolyether and the content of the salt are the same as those explained in the composition of the present disclosure.

[0074] In the electrolyte solution of the present disclosure, the fluoropolyether is usually used as a solvent. The content of the fluoropolyether is preferably 70% by volume or more, more preferably 80% by volume or more, and even more preferably 90% by volume or more, relative to the solvent. There is no particular upper limit, and it may be 100% by mass.

[0075] In the electrolyte solution of the present disclosure, a solvent other than the fluoropolyether may be used. Examples of the solvent other than the fluoropolyether include those conventionally known as solvents for non-aqueous secondary batteries, such as carbonate-based solvents, ester-based solvents, ether-based solvents, and fluorobenzene-based solvents. Examples of the carbonate-based solvent include cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, and fluoroethylene carbonate, and chain carbonates such as dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. Examples of the ester-based solvent include cyclic esters such as γ-butyrolactone and γ-valerolactone, and chain esters such as methyl acetate and ethyl acetate. Examples of the ether-based solvent include cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran, and chain ethers such as dimethoxyethane and glyme-based compounds. Examples of glyme-based compounds include diethylene glycol diethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether. Examples of fluorobenzene-based solvents include 1,3-difluorobenzene, 1,2,4-trifluorobenzene, and 1,2,3,4-tetrafluorobenzene. These may be used alone or in combination of two or more. In the present disclosure, ether-based solvents are preferred, chain ethers are more preferred, and glyme-based compounds are even more preferred. The compounds described herein may also be used in small amounts as additives.

[0076] The ionic conductivity of the electrolyte of the present disclosure is preferably 1.0×10 -7 S / cm or more, preferably 1.0×10 -6 S / cm or more, more preferably 1.0×10 -5 The upper limit is not particularly limited, but is preferably 1.0×10 -3 S / cm or less. The above ionic conductivity is a value obtained by measurement at 25°C using a Mettler Toledo SevenCompact S230.

[0077] The Li-ion transport number of the electrolyte solution of the present disclosure is preferably 0.2 or more, more preferably 0.25 or more, and even more preferably 0.3 or more. The upper limit is not particularly limited, but is preferably 0.5 or less. The Li ion transport number is a value determined by the following method (pulsed magnetic field gradient NMR measurement). Pulsed magnetic field gradient NMR measurements were performed at 25°C using a JEOL JNM-ECA400WB. 7 The self-diffusion coefficient D is

number

[0078] <Polymer electrolyte> The present disclosure also relates to a polymer electrolyte comprising the electrolyte of the present disclosure.

[0079] The polymer electrolyte of the present disclosure includes, for example, a gel electrolyte in which a polymer material is plasticized with the electrolytic solution of the present disclosure.

[0080] Examples of the polymer material include conventionally known polyethylene oxide, polypropylene oxide, and modified products thereof (JP Patent Publication Nos. 8-222270 and 2002-100405); polyacrylate polymers, polyacrylonitrile, fluororesins such as polyvinylidene fluoride and vinylidene fluoride-hexafluoropropylene copolymers (JP Patent Publication Nos. 4-506726, 8-507407, and 10-294131); and complexes of such fluororesins and hydrocarbon resins (JP Patent Publication Nos. 11-35765 and 11-86630). In particular, polyvinylidene fluoride and vinylidene fluoride-hexafluoropropylene copolymers are preferred.

[0081] <Electrochemical devices> The present disclosure also relates to an electrochemical device comprising the electrolyte of the present disclosure or the polymer electrolyte of the present disclosure.

[0082] The electrochemical device of the present disclosure preferably comprises a positive electrode, a negative electrode, etc., and more specifically, is preferably a secondary battery comprising these, and is particularly preferably a lithium ion secondary battery.

[0083] The positive electrode active material used in the positive electrode is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but for example, a material containing an alkali metal and at least one transition metal is preferable. Specific examples include an alkali metal-containing transition metal complex oxide and an alkali metal-containing transition metal phosphate compound. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal complex oxide that produces high voltage. Examples of the alkali metal ion include lithium ion, sodium ion, potassium ion, etc., and lithium ion is preferable.

[0084] Examples of the alkali metal-containing transition metal composite oxide include: Formula: M a Mn 2-b M 1 b O4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 c O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3 is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), in which M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0085] Among these, MCoO2, MMnO2, MNiO2, MMn2O4, and MNi are the most popular because they can provide high energy density and high output secondary batteries. 0.8 Co 0.15 Al 0.05 O2 or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and the like are preferred, and a compound represented by the following general formula is preferred. MNi h Co i Mnj M 5 k O2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.

[0086] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following general formula: M e M 4 f (PO4) g (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0087] The transition metal of the alkali metal-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main part of these lithium transition metal phosphate compounds is replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. The lithium-containing transition metal phosphate compound is preferably one having an olivine structure.

[0088] Other examples of the positive electrode active material include lithium-nickel-based composite oxides. The lithium-nickel-based composite oxides are represented by the following general formula: Li y Ni 1-x M x O2 (wherein x is 0.01≦x≦0.7, y is 0.9≦y≦2.0, and M is a metal atom (excluding Li and Ni)) is preferred.

[0089] Other positive electrode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3, etc. In particular, M2MnO3, MNi 0.5 Mn 1.5 A positive electrode active material such as O2 is preferable because the crystal structure does not collapse even when the secondary battery is operated at a voltage exceeding 4.4 V or at a voltage of 4.6 V or more. Therefore, an electrochemical device such as a secondary battery using a positive electrode material containing the above-mentioned positive electrode active material is preferable because the remaining capacity is unlikely to decrease and the resistance increase rate is unlikely to change even when stored at high temperatures, and the battery performance is not deteriorated even when operated at high voltages.

[0090] Other positive electrode active materials include M2MnO3 and MM 6 O2 (wherein M is at least one metal selected from the group consisting of Li, Na, and K; M 6 Also included are solid solution materials with transition metals such as Co, Ni, Mn, and Fe.

[0091] The solid solution material is, for example, a material represented by the general formula M x [Mn (1-y) M 7 y ]O z In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 7It consists of at least one metal element other than M and Mn, and contains one or more elements selected from the group consisting of, for example, Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 A manganese-containing solid solution material in which LiNiO2 or LiCoO2 is solid-solved based on Li2MnO3 such as Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O2 is preferable because it can provide an alkali metal ion secondary battery having a high energy density.

[0092] Also, it is preferable to include lithium phosphate in the positive electrode active material because the continuous charging characteristics are improved. There is no limitation on the use of lithium phosphate, but it is preferable to mix and use the above-mentioned positive electrode active material and lithium phosphate. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and still more preferably 0.5% by mass or more, and the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and still more preferably 5% by mass or less, based on the total of the above-mentioned positive electrode active material and lithium phosphate.

[0093] Also, a material in which a substance having a composition different from this adheres to the surface of the above-mentioned positive electrode active material may be used. Examples of the surface-adhering substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0094] The above-mentioned surface-attaching substance can be attached to the surface of the positive electrode active material by, for example, a method of dissolving or suspending in a solvent, impregnating and adding to the positive electrode active material, and drying, a method of dissolving or suspending a surface-attaching substance precursor in a solvent, impregnating and adding to the positive electrode active material, and then reacting by heating, etc., a method of adding to a positive electrode active material precursor and simultaneously baking, etc. When carbon is attached, a method of mechanically attaching carbonaceous material in the form of, for example, activated carbon, etc., afterwards can also be used.

[0095] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and even more preferably 10 ppm or more by mass relative to the positive electrode active material, and is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less by mass relative to the positive electrode active material. The surface-attached substance can suppress the oxidation reaction of the electrolyte on the surface of the positive electrode active material and can improve the battery life, but if the amount of attachment is too small, the effect is not fully exerted, and if it is too large, the ingress and egress of lithium ions is inhibited, which may increase the resistance.

[0096] The shape of the particles of the positive electrode active material may be any of the conventional shapes such as block, polyhedron, sphere, oval sphere, plate, needle, column, etc. Primary particles may be aggregated to form secondary particles.

[0097] The tap density of the positive electrode active material is preferably 0.5 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 1.0 g / cm 3That is all. If the tap density of the positive electrode active material is below the lower limit, the amount of dispersion medium required during the formation of the positive electrode active material layer increases, and the amount of conductive material and binder required also increases, restricting the filling rate of the positive electrode active material in the positive electrode active material layer and possibly restricting the battery capacity. By using a composite oxide powder with a high tap density, a high density positive electrode active material layer can be formed. Generally, the higher the tap density, the better, and there is no particular upper limit, but if it is too high, the diffusion of lithium ions in the positive electrode active material layer using the electrolyte as a medium becomes rate-limiting, and the load characteristics may be easily deteriorated, so that the upper limit is preferably 4.0 g / cm. 3 Less than or equal to 3.7 g / cm 3 More preferably, 3.5 g / cm 3 The following is the result. The above tap density is the powder packing density (tap density) g / cm when 5 to 10 g of the positive electrode active material powder is placed in a 10 ml glass measuring cylinder and tapped 200 times with a stroke of approximately 20 mm. 3 is required.

[0098] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter when primary particles are aggregated to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, even more preferably 0.8 μm or more, and most preferably 1.0 μm or more, and is preferably 30 μm or less, more preferably 27 μm or less, even more preferably 25 μm or less, and most preferably 22 μm or less. If it is below the lower limit, a high tap density product may not be obtained, and if it exceeds the upper limit, it may take time for lithium to diffuse within the particles, resulting in problems such as a decrease in battery performance. Here, by mixing two or more types of the positive electrode active materials having different median diameters d50, the filling property during positive electrode production can be further improved.

[0099] The median diameter d50 is measured by a known laser diffraction / scattering type particle size distribution analyzer. When using HORIBA's LA-920 as the particle size distribution analyzer, a 0.1% by mass aqueous solution of sodium hexametaphosphate is used as the dispersion medium for the measurement, and the measurement is performed after ultrasonic dispersion for 5 minutes with a measurement refractive index set to 1.24.

[0100] In the case where the primary particles are aggregated to form secondary particles, the average primary particle diameter of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, even more preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which may adversely affect the powder packing property or greatly reduce the specific surface area, and therefore the battery performance such as output characteristics may be likely to decrease. On the other hand, if the lower limit is exceeded, problems such as poor reversibility of charge and discharge may occur due to underdeveloped crystals. The average primary particle diameter is measured by observation using a scanning electron microscope (SEM). Specifically, in a photograph at a magnification of 10,000 times, the longest intercept value of a horizontal line at the left and right boundaries of a primary particle is determined for any 50 primary particles, and the average value is calculated.

[0101] The BET specific surface area of ​​the positive electrode active material is preferably 0.1 m 2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more, and the upper limit is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease, whereas if it is larger, it is difficult to increase the tap density, and problems may easily occur in the processability when forming the positive electrode active material layer. The BET specific surface area is defined as a value measured by a nitrogen adsorption BET one-point method using a gas flow method, using a surface area meter (e.g., a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.) after pre-drying a sample at 150°C for 30 minutes under a nitrogen flow and then using a nitrogen / helium mixed gas accurately adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3.

[0102] When used in large-sized lithium-ion secondary batteries for hybrid vehicles or distributed power sources, high output is required, so it is preferable that the particles of the positive electrode active material are mainly secondary particles. The particles of the positive electrode active material preferably have an average secondary particle diameter of 40 μm or less and contain 0.5 to 7.0 volume % of fine particles having an average primary particle diameter of 1 μm or less. By containing fine particles having an average primary particle diameter of 1 μm or less, the contact area with the electrolyte increases, and the diffusion of lithium ions between the electrode mixture and the electrolyte can be made faster, resulting in improved output performance of the battery.

[0103] The manufacturing method of the positive electrode active material is generally used as the manufacturing method of inorganic compounds.In particular, various methods can be considered for making spherical or oval-spherical active material, for example, the raw material of transition metal is dissolved or crushed and dispersed in a solvent such as water, and while stirring, pH is adjusted to make and recover spherical precursor, which is dried as necessary, and then LiOH, Li2CO3, LiNO3, or other Li source is added and calcined at high temperature to obtain active material.

[0104] The above positive electrode active materials may be used alone or in any combination or ratio of two or more different compositions. In this case, a preferred combination is LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 Examples of such a combination include a combination with a ternary system such as O2, a combination of LiCoO2 and LiMn2O4 or a combination in which a portion of the Mn is replaced with another transition metal, or a combination of LiFePO4 and LiCoO2 or a combination in which a portion of the Co is replaced with another transition metal.

[0105] The content of the positive electrode active material is preferably 50 to 99.5% by mass of the electrode mixture, more preferably 80 to 99% by mass, in terms of high battery capacity. The content in the positive electrode active material layer is preferably 80% by mass or more, more preferably 82% by mass or more, and particularly preferably 84% by mass or more. The upper limit is preferably 99% by mass or less, more preferably 98% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the strength of the positive electrode may be insufficient.

[0106] The negative electrode active material used in the negative electrode is not particularly limited, and examples thereof include those containing carbonaceous materials such as lithium metal, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon, silicon-containing compounds such as silicon and silicon alloys, Li4Ti5O 12 Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.

[0107] The negative electrode active material preferably contains silicon as a constituent element, which allows a high-capacity battery to be produced.

[0108] The silicon-containing material includes silicon particles, particles having a structure in which silicon particles are dispersed in a silicon-based compound, and silicon-based compounds having the general formula SiO x Silicon oxide particles represented by the formula (0.5≦x≦1.6) or a mixture thereof are preferred. By using these, a negative electrode mixture for a lithium ion secondary battery having a higher initial charge / discharge efficiency, a higher capacity, and excellent cycle characteristics can be obtained.

[0109] In the present disclosure, silicon oxide is a general term for amorphous silicon oxide. Silicon oxide before disproportionation has the general formula SiO x(0.5≦x≦1.6), where x is preferably 0.8≦x<1.6, and more preferably 0.8≦x<1.3. This silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon to produce silicon monoxide gas, and then cooling and precipitating the gas.

[0110] Particles having a structure in which silicon particles are dispersed in a silicon-based compound can be prepared, for example, by a method in which silicon particles are mixed with a silicon-based compound and then fired, or by a method in which a silicon-based compound having the general formula SiO x The silicon oxide particles before disproportionation represented by the formula (1) are heat-treated in an inert non-oxidizing atmosphere such as argon at a temperature of 400°C or higher, preferably 800 to 1,100°C, to carry out a disproportionation reaction. The material obtained by the latter method is particularly suitable because silicon microcrystals are uniformly dispersed. The size of silicon nanoparticles can be set to 1 to 100 nm by the above-mentioned disproportionation reaction. The silicon oxide in the particles having a structure in which silicon nanoparticles are dispersed in silicon oxide is preferably silicon dioxide. The dispersion of silicon nanoparticles (crystals) in amorphous silicon oxide can be confirmed by a transmission electron microscope.

[0111] The physical properties of the silicon-containing particles can be appropriately selected depending on the desired composite particles. For example, the average particle size is preferably 0.1 to 50 μm, more preferably 0.2 μm or more as the lower limit, and even more preferably 0.5 μm or more as the upper limit. The average particle size is represented by the weight average particle size in particle size distribution measurement by laser diffraction method. BET specific surface area is 0.5 to 100 m 2 / g is preferable, and 1 to 20m 2 / g is more preferable. 2 / g or more, there is no risk of the adhesiveness decreasing when applied to an electrode, resulting in a decrease in battery characteristics. 2 / g or less, the proportion of silicon dioxide on the particle surface becomes large, and there is no risk of a decrease in battery capacity when used as a negative electrode material for a lithium ion secondary battery.

[0112] The silicon-containing particles are coated with carbon to impart electrical conductivity, which leads to improved battery characteristics. Methods for imparting electrical conductivity include mixing with conductive particles such as graphite, coating the surfaces of the silicon-containing particles with a carbon coating, and combining both of these methods. The carbon coating method is preferred, and chemical vapor deposition (CVD) is more preferred.

[0113] In order to increase the capacity of the resulting electrode mixture, the content of the negative electrode active material is preferably 40% by mass or more, more preferably 50% by mass or more, and particularly preferably 60% by mass or more in the electrode mixture, and the upper limit is preferably 99% by mass or less, more preferably 98% by mass or less.

[0114] The electrode mixture constituting the positive electrode or the negative electrode may contain a conductive assistant. The conductive assistant is not particularly limited, but examples thereof include metal materials such as copper, nickel, and gold, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as VGCF, etc. These may be used alone or in any combination and ratio of two or more.

[0115] The conductive assistant is used in an amount of usually 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 1% by mass or more, in the electrode mixture, and usually 50% by mass or less, preferably 30% by mass or less, more preferably 15% by mass or less.

[0116] The electrode mixture may contain a thickener. Examples of the thickener include carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, ethylcellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, polyvinylpyrrolidone, and salts thereof, etc. One type may be used alone, or two or more types may be used in any combination and ratio.

[0117] The thickener is used in an amount of usually 0.1% by mass or more, preferably 0.2% by mass or more, and more preferably 0.3% by mass or more, relative to the electrode active material, and is usually used in an amount of 5% by mass or less, preferably 3% by mass or less, and more preferably 2% by mass or less.

[0118] The electrode mixture may contain a binder. The binder is not particularly limited, and examples thereof include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, chitosan, alginic acid, polyacrylic acid, polyimide, cellulose, and nitrocellulose; rubber-like polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or hydrogenated products thereof; and EPDM (ethylene-propylene-diene ternary copolymers). Examples of suitable polymers include thermoplastic elastomers such as styrene-ethylene-butadiene-styrene copolymers, styrene-isoprene-styrene block copolymers, and hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride, vinylidene fluoride copolymers, polytetrafluoroethylene, and tetrafluoroethylene-ethylene copolymers; and polymer compositions having ionic conductivity for alkali metal ions (especially lithium ions). These may be used alone or in any combination and ratio of two or more.

[0119] The binder is used in an amount of usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 0.6% by mass or more, and usually 20% by mass or less, preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less, based on the electrode active material.

[0120] The positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the positive electrode active material. The material of the positive electrode current collector includes metals such as aluminum, titanium, tantalum, stainless steel, nickel, and the like, and metal materials such as alloys thereof; carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or its alloys, are preferred.

[0121] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0122] In addition, it is also preferable that the surface of the current collector is coated with a conductive assistant from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver.

[0123] The positive electrode may be manufactured by a conventional method, for example, a method in which an electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0124] The density of the positive electrode mixture sheet is preferably 2.50 g / cm 3 More preferably, 2.80 g / cm 3More preferably, 3.00 g / cm 3 or more, and preferably 3.80 g / cm 3 Less than or equal to 3.70 g / cm 3 More preferably, 3.60 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current density, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.

[0125] The thickness of the positive electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture layer minus the thickness of the metal foil of the current collector is, as a lower limit, preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less, on one side of the current collector.

[0126] The negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the negative electrode active material. The material of the current collector for the negative electrode includes metals such as copper, nickel, titanium, tantalum, and stainless steel, or metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly copper, nickel, or alloys thereof, are preferred.

[0127] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0128] The negative electrode may be produced by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0129] The density of the negative electrode mixture is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More preferably, it is 2.0 g / cm 3 Less than or equal to 1.9 g / cm 3 More preferably, 1.8 g / cm 3 The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current density, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.

[0130] The thickness of the negative electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture layer minus the thickness of the metal foil of the current collector is, as a lower limit, preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less on one side of the current collector.

[0131] The secondary battery containing the electrolyte solution of the present disclosure preferably further comprises a separator. The material and shape of the separator are not particularly limited as long as they are stable to the electrolyte solution and have excellent liquid retention, and any known separator can be used. Among them, it is preferable to use a material formed of a material stable to the electrolyte solution, such as a resin, glass fiber, or inorganic material, and to use a porous sheet or nonwoven fabric having excellent liquid retention.

[0132] Examples of materials that can be used for the resin and glass fiber separator include polyolefins such as polyethylene and polypropylene, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, and glass filters. These materials may be used alone or in any combination and ratio, such as polypropylene / polyethylene two-layer film and polypropylene / polyethylene / polypropylene three-layer film. Among these, the separator is preferably a porous sheet or nonwoven fabric made of polyolefins such as polyethylene and polypropylene, because of its excellent electrolyte permeability and shutdown effect.

[0133] The thickness of the separator is arbitrary, but is usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is thinner than the above range, the insulating properties and mechanical strength may be reduced. If the separator is thicker than the above range, not only may the battery performance such as rate characteristics be reduced, but also the energy density of the entire electrolyte battery may be reduced.

[0134] On the other hand, examples of inorganic materials that can be used include oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate, and these are in particulate or fibrous form.

[0135] As for the form, a thin film such as a nonwoven fabric, a woven fabric, or a microporous film is used. In the thin film form, a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm is preferably used. In addition to the above independent thin film form, a separator can be used in which a composite porous layer containing the above inorganic particles is formed on the surface layer of a positive electrode and / or a negative electrode using a resin binder. For example, a porous layer can be formed on both sides of a positive electrode using alumina particles with a 90% particle size of less than 1 μm and a fluororesin as a binder.

[0136] The material of the exterior case is not particularly limited as long as it is a material that is stable against the electrolyte used. Specifically, metals such as nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminate film of resin and aluminum foil (laminate film) are used. From the viewpoint of weight reduction, metals such as aluminum or aluminum alloy, and laminate films are preferably used.

[0137] In the case of an exterior case using metals, there are cases in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed structure, or cases in which the metals are used via a resin gasket to form a crimped structure. In the case of an exterior case using the laminate film, there are cases in which the resin layers are heat-sealed together to form a sealed structure. In order to improve the sealing property, a resin different from the resin used in the laminate film may be interposed between the resin layers. In particular, when the resin layer is heat-sealed via a current collecting terminal to form a sealed structure, the joining between the metal and the resin is performed, so that a resin having a polar group or a modified resin into which a polar group has been introduced is preferably used as the interposed resin.

[0138] The shape of the secondary battery using the above-mentioned electrolyte solution is arbitrary, and examples of the shape include a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. The shapes and configurations of the positive electrode, the negative electrode, and the separator can be changed according to the shape of each battery.

[0139] <Fluoropolyether> The present disclosure also relates to a fluoropolyether represented by formula (2A): (2A)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (In the formula, Ra 2 is a polyoxyalkylene containing 4 to 50 oxyalkylene units not containing fluorine, Ra 2each oxyalkylene unit is independently -CHCHO- or -CHCH(J)O-; Each J is independently an alkyl group or an aryl group; Rb 2 are each independently a fluoropolyether group represented by the following formula (4A): R 2 are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4A)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0140] The above-mentioned fluoropolyether is a novel compound that dissolves salts and has sufficient ionic conductivity, and therefore can be used as a solvent for an electrolyte. Its use in an electrolyte can improve the high-temperature durability (particularly, cycle performance at high temperatures) of an electrochemical device. It is also flame-retardant and has higher electrochemical stability than ordinary electrolyte solvents, and therefore can improve the safety of an electrochemical device. Furthermore, it has a good transport number.

[0141] The preferred forms of the fluoropolyether are the same as those of the fluoropolyether of formula (2) above.

[0142] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0143] Next, the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0144] The following compounds were used: Compounds 1-1 to 1-9 were liquid at 25°C. <Compound 1-1> CH3O(CH2CH2O) x1 CH2CF2(OCF2CF2) y (OCF2) z OCF2CH2O(CH2CH2O) x2 CH3 (x1:4, y: average 12.3, z: average 10.2, x2:4, (CH2CH2O) x1 Number average molecular weight: 176, (CH2CH2O) x2 Number average molecular weight: 176) <Compound 1-2> Compound with the same structure as compound 1-1 (x1: average 8.4, y: average 12.3, z: average 10.2, x2: average 8.4, (CH2CH2O) x1 Number average molecular weight: 400, (CH2CH2O) x2 Number average molecular weight: 400) <Compound 1-3> CF2(CF3)CF2(OCF(CF3)CF2) x OCF(CF3)CH2O(CH2CH2O) y CH3 (x: average 7, y: 4, (CH2CH2O) y Number average molecular weight: 176) <Compound 1-4> Compounds with the same structure as Compound 1-3 (x: average 9.4, y: 4, (CH2CH2O) y Number average molecular weight: 176) <Compound 1-5> Compounds with the same structure as Compound 1-3 (x: average 14.3, y: 4, (CH2CH2O) y Number average molecular weight: 176) <Compound 1-6> CF3CF2(OCF2CF2CF2) x OCF2CF2CH2O(CH2CH2O) y CH3 (x: average 11, y: 4, (CH2CH2O) yNumber average molecular weight: 176) <Compound 1-7> CF3CF2(OCF2CF2) x (OCF2) y OCF2CH2O(CH2CH2O) z CH3 (x: average 15.5, y: average 13.0, z: 4, (CH2CH2O) z Number average molecular weight: 176) <Compound 1-8> CF3CF2(OCF2CF2) x1 (OCF2) y1 OCF2CH2O(CH2CH2O) z CH2CF2(OCF2CF2) x2 (OCF2) y2 OCF2CF3 (x1: average 15.5, y1: average 13.0, z: average 4.1, x2: average 15.5, y2: average 13.0, (CH2CH2O) z Number average molecular weight: 200) <Compound 1-9> CF2(CF3)CF2(OCF(CF3)CF2) x OCF(CF3)CH2O(CH2CH2O) y CH2C(CF3)F(OCF2C(CF3)F) z OCF2C(CF3)F2 (x: average 7, y: average 4.1, z: average 7, (CH2CH2O) y Number average molecular weight: 200)

[0145] <Compound 2-1> Ethyl methyl carbonate (EMC, Kishida Chemical Co., Ltd.) <Compound 2-2> Polyethylene glycol 200 (Tokyo Chemical Industry Co., Ltd.) <Compound 2-3> Poly(ethylene glycol methyl ether) 220 (Kanto Chemical Co., Ltd.) <Compound 2-4> Fomblin Oil M07 (Solvay) RO(CF2CF2O) x (CF2O)y R (R:CF3 and CF2CF3 exist in an average ratio of 1:0.21, x:average 29.0, y:32.2) <Compound 2-5> Fluorolink E10H (Solvay) HO(CH2CH2O) x1 CH2CF2O(CF2CF2O) x2 (CF2O) y CF2CH2O(CH2CH2O) x3 H (x1: average 1.27, y: average 8.16, x2: average 7.09, x3: average 1.27) <Compound 2-6> Fluorolink D (Solvay) HOCH2CF2O(CF2CF2O) x (CF2O) y CF2CH2OH (x: average 12.0, y: average 10.8)

[0146] (Synthesis Example 1) Synthesis of Compound 1-1 In a nitrogen-substituted reaction vessel, 600 mg of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 15.3 mmol), 30 g of 1,3-bis(trifluoromethyl)benzene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 10 g of fluoropolyether both-terminal alcohol (manufactured by Solvay, Fomblin D2, 5.1 mmol) were added and heated and stirred at 70 ° C for 3 hours. The internal temperature was raised to 65 ° C, and 5.5 g of triethylene glycol-2-bromoethyl methyl ether (manufactured by Tokyo Chemical Industry Co., Ltd., 20.4 mmol) was dropped from the dropping funnel over 10 minutes, and the mixture was heated and stirred for 6 hours. After returning to room temperature, 5 ml of 1N hydrochloric acid was added to the reaction solution and stirred for 3 hours. This solution was washed four times with pure water, and 2 g of magnesium sulfate was added to the separated organic layer and dried. The volatile matter was removed from the treated solution from which magnesium sulfate had been removed by filtration, and the solution was further dried at 100 ° C for 3 hours to obtain compound 1-1.

[0147] (Synthesis Example 2) Synthesis of tosylated polyethylene glycol monomethyl ether In a nitrogen-substituted reaction vessel, 8.0 g of polyethylene glycol monomethyl ether 400 (Tokyo Chemical Industry Co., Ltd., average molecular weight 380-420, 20.0 mmol), 25 mL of tetrahydrofuran (Tokyo Chemical Industry Co., Ltd.), and 4.7 g of p-toluenesulfonyl chloride (Tokyo Chemical Industry Co., Ltd., 25 mmol) were added and stirred until homogenous. A solution of 3.4 g of potassium hydroxide (FUJIFILM Wako Pure Chemical Industries, Ltd., 60 mmol) / 10 mL of pure water was added to a reaction vessel in an ice water bath, and after stirring for 10 minutes, the ice water bath was removed and the mixture was stirred at room temperature for 12 hours. The reaction solution was poured into a mixture of 30 mL of ice water / 60 mL of methylene chloride, and the aqueous layer was extracted three times with methylene chloride. 8 g of magnesium sulfate was added to the separated organic layer and dried. Volatiles were removed from the treated solution from which magnesium sulfate had been removed by filtration, and a tosylated polyethylene glycol monomethyl ether was obtained.

[0148] (Synthesis Example 3) Synthesis of Compound 1-2 Compound 1-2 was obtained by reacting the tosylated polyethylene glycol monomethyl ether synthesized in Synthesis Example 2 under the reaction conditions of Synthesis Example 1, instead of triethylene glycol-2-bromoethyl methyl ether.

[0149] (Synthesis Example 4) Synthesis of Compound 1-3 In a nitrogen-substituted reaction vessel, 600 mg of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 15.3 mmol), 30 g of 1,3-bis(trifluoromethyl)benzene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 5.1 g of fluoropolyether one-terminated alcohol (manufactured by Unichem Co., Ltd., perfluoropolyether modified, molecular weight 1500, 5.1 mmol) were added and heated and stirred at 70 ° C for 3 hours. The internal temperature was set to 65 ° C, and 2.8 g of triethylene glycol-2-bromoethyl methyl ether (manufactured by Tokyo Chemical Industry Co., Ltd., 10.0 mmol) was dropped from the dropping funnel over 10 minutes, and the mixture was heated and stirred for 6 hours. After returning to room temperature, 5 ml of 1N hydrochloric acid was added to the reaction solution and stirred for 3 hours. This solution was washed four times with pure water, and 2 g of magnesium sulfate was added to the separated organic layer and dried. The volatile matter was removed from the treated solution from which magnesium sulfate had been removed by filtration, and the solution was further dried at 100 ° C for 3 hours to obtain compound 1-3.

[0150] (Synthesis Example 5) Synthesis of Compound 1-4 Compound 1-4 was obtained by carrying out the same reaction as in Synthesis Example 4, except that the fluoropolyether alcohol terminated at one end was replaced with a perfluoropolyether modified product having a molecular weight of 2000, manufactured by Unichem Co., Ltd.

[0151] (Synthesis Example 6) Synthesis of Compound 1-5 Compound 1-5 was obtained by carrying out the same reaction as in Synthesis Example 4, except that the fluoropolyether one-terminated alcohol was replaced with a perfluoropolyether modified product having a molecular weight of 3,000, manufactured by Unichem Co., Ltd.

[0152] (Synthesis Example 7) Synthesis of Compound 1-6 Compound 1-6 was obtained by carrying out the reaction in the same manner as in Synthesis Example 4, except that the fluoropolyether one-terminated alcohol was replaced with Demnum SA manufactured by Daikin Industries, Ltd.

[0153] (Synthesis Example 8) Synthesis of Compound 1-7 Compound 1-7 was obtained by the same reaction as in Synthesis Example 4, except that the fluoropolyether one-terminated alcohol was replaced with Fluorolink ZMF-402 manufactured by Solvay.

[0154] (Synthesis Example 9) Synthesis of polyethylene glycol with both terminal tosylation In a nitrogen-substituted reaction vessel, 4.0 g of polyethylene glycol 200 (Tokyo Chemical Industry Co., Ltd., average molecular weight 190-210, 20.0 mmol), 25 mL of tetrahydrofuran (Tokyo Chemical Industry Co., Ltd.), and 9.4 g of p-toluenesulfonyl chloride (Tokyo Chemical Industry Co., Ltd., 50 mmol) were added and stirred until homogenous. In an ice-water bath, 6.7 g of potassium hydroxide (Fujifilm Wako Pure Chemical Industries, Ltd., 120 mmol) was added, and after stirring for 10 minutes, the ice-water bath was removed and the mixture was stirred at room temperature for 12 hours. The reaction solution was poured into a mixture of 30 mL of ice water / 60 mL of methylene chloride, and the aqueous layer was extracted three times with methylene chloride. 5 g of magnesium sulfate was added to the collected organic layer and dried. The volatile matter was removed from the treated solution by filtration to obtain the desired polyethylene glycol with both terminals tosylated.

[0155] (Synthesis Example 10) Synthesis of Compound 1-8 In a nitrogen-substituted reaction vessel, 600 mg of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 15.3 mmol), 30 g of 1,3-bis(trifluoromethyl)benzene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 20.4 g of fluoropolyether one-terminated alcohol (manufactured by Solvay, Fluorolink ZMF-402, 5.1 mmol) were added and heated and stirred at 70 ° C for 3 hours. The internal temperature was set to 65 ° C, and 1.3 g (2.5 mmol) of the polyethylene glycol both-terminated tosylated body obtained in Synthesis Example 9 was dissolved in 5 g of 1,3-bis(trifluoromethyl)benzene and dropped from the dropping funnel over 10 minutes, and the mixture was heated and stirred for 6 hours. After returning to room temperature, 5 ml of 1N hydrochloric acid was added to the reaction solution and stirred for 3 hours. This solution was washed four times with pure water, and 2 g of magnesium sulfate was added to the separated organic layer and dried. The magnesium sulfate was removed by filtration, and the volatile matter was distilled off from the treated solution. The solution was then dried at 100°C for 3 hours to obtain compound 1-8.

[0156] (Synthesis Example 11) Synthesis of Compound 1-9 Compound 1-9 was obtained by carrying out the same reaction as in Synthesis Example 10, except that the fluoropolyether alcohol terminated at one end was replaced with a perfluoropolyether modified product having a molecular weight of 1,500, manufactured by Unichem Co., Ltd.

[0157] <Experiment 1> Examples 1 to 11, Comparative Examples 1 to 6 (Preparation of composition (electrolyte) containing lithium salt) A composition containing 5 mass % of lithium salt was obtained by adding a compound shown in component 1 in Table 1 and lithium salt lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, manufactured by Tokyo Chemical Industry Co., Ltd.) and stirring for 24 hours at 45° C. In addition, when the compound shown in component 2 in Table 1 was contained, components 1 and 2 were mixed in the volume ratio shown in Table 1, and then the lithium salt was added to obtain a composition containing 5 mass % of lithium salt.

[0158] (Non-flammability test) The non-flammability (non-ignition property) of the composition was examined by the following method. (Sample preparation) A strip of cellulose paper (width 15 mm, length 320 mm, thickness 0.04 mm) was thoroughly immersed in the composition produced in the above Examples or Comparative Examples and then removed to prepare a sample. (Test Method) The sample was fixed on a metal stand, and a lighter flame was brought close to one end of the sample and held there for one second to check whether or not it ignited. The evaluation criteria were as follows: ◯ if the product did not ignite (non-flammable) or if it ignited but the fire went out immediately (self-extinguishing), and × if the product ignited and continued to burn.

[0159] (Reduction resistance test) A lithium metal piece was placed in the composition and left for one week, and the discoloration of the surface of the lithium metal piece was visually observed. If there was no discoloration, it was evaluated as having good reduction resistance and marked with a circle, and if there was discoloration, it was evaluated as having poor reduction resistance and marked with a cross.

[0160] (Salt solubility test) The prepared compositions were visually observed and rated as follows: ◯ if the solution was homogeneous, Δ if the salt appeared to be dissolved but some of the salt remained undissolved, and × if no salt was dissolved at all.

[0161] [Table 1]

[0162] <Experiment 2> Examples 12 to 25, Comparative Examples 7 to 12 (Preparation of composition (electrolyte) containing lithium salt) Solutions were prepared in the same manner as in Experiment 1 using the combinations of compounds and salts shown in Tables 2 to 4. The salts used are as follows. LiTFSI: Lithium bis(trifluoromethanesulfonyl)imide (Tokyo Chemical Industry Co., Ltd.) LiFSI: Lithium bis(fluorosulfonyl)imide (Tokyo Chemical Industry Co., Ltd.) LiPF6: Lithium hexafluorophosphate (Kanto Denka Kogyo Co., Ltd.)

[0163] (Ionic conductivity measurement) Ionic conductivity was measured at 25°C using a Mettler Toledo SevenCompact S230. The measuring device was calibrated in advance using a standard solution of 12.88 mS / cm.

[0164] (Li ion transport number) The Li-ion transport number was determined by the following method (pulsed magnetic field gradient NMR measurement). Pulsed magnetic field gradient NMR measurements were performed at 25°C using a JEOL JNM-ECA400WB. 7 The self-diffusion coefficient D is

number

[0165] (Production of coin-type lithium-ion secondary batteries) <Preparation of positive electrode> Li(Ni 0.6 Mn 0.2 Co 0.2 95% by mass of 1,2-dichloroethane (1,2,3-trifluoroethylene) oxide, 3% by mass of acetylene black as a conductive assistant, and 2% by mass of polyvinylidene fluoride (PVdF) as a binder were mixed in NMP solvent to form a slurry. The obtained slurry was uniformly applied to an aluminum foil having a thickness of 20 μm, dried (110°C, 30 minutes), and then compressed and formed by applying a load using a press machine to prepare a positive electrode sheet integrated with a current collector, which was then punched out to a predetermined size. The electrode mixture thickness was 57 μm and the density was 2.8 g / cc.

[0166] <Preparation of negative electrode> 98 parts by mass of carbonaceous material (graphite) was mixed with 1 part by mass of aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) and 1 part by mass of aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 50% by mass) as a thickener and binder, and the mixture was mixed in a disperser to form a slurry. The obtained slurry was applied to a copper foil having a thickness of 10 μm, dried, and rolled in a press machine, and then punched out to the desired size.

[0167] <Coin cell production> The above positive and negative electrodes were arranged opposite to each other via a 20 μm-thick microporous polyethylene film (separator), and an electrolyte solution having the composition obtained in the preparation of a composition (electrolyte solution) containing a lithium salt was used as the electrolyte solution. The battery was kept in a vacuum state until the non-aqueous electrolyte solution sufficiently permeated the separator and the like, and then the battery was sealed, pre-charged, and aged to produce a coin-type lithium ion secondary battery.

[0168] (Weight discharge capacity characteristics / high temperature cycle characteristics) The lithium ion secondary battery produced above was charged at 80°C with a constant current and constant voltage (cut at 0.01C) to 4.2V at a current equivalent to 0.05C, and then discharged to 3V at a constant current of 0.05C, which constitutes one cycle. The initial discharge capacity was calculated from the discharge capacity at the third cycle. The gravimetric discharge capacity characteristics were calculated using the following formula. ·Calculation formula for weight discharge capacity characteristics Weight discharge capacity characteristic (mAh / g) = Initial discharge capacity (mAh) / Weight of active material in the positive electrode mixture (g) The weight discharge capacity characteristics were ranked as follows: A:165mAh / g or more B: 155mAh / g or more and less than 165mAh / g C: 145mAh / g or more and less than 155mAh / g D: Less than 145mAh / g After that, the battery was cycled up to 10 cycles, and the capacity retention rate was calculated using the following formula. Capacity retention rate calculation formula Capacity retention rate (%) = Discharge capacity after 10 cycles (mAh) / Discharge capacity after 3 cycles (mAh) x 100 The capacity retention rate (high temperature cycle characteristics) was ranked as follows. A: 95% or more B: 90% or more but less than 95% C: 85% to less than 90% D: Less than 85%

[0169] [Table 2]

[0170] The values ​​marked with "E" in Table 2 represent exponents. For example, ".E‐04" means "×10 -4 The same applies to Tables 3 and 4 below.

[0171] [Table 3] [Table 4]

[0172] <Preparation of polymer electrolyte membrane> 10 g of polyethylene oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., molecular weight 1,000,000), 4 g of compound 1-1, and 0.2 g of LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) (manufactured by Tokyo Chemical Industry Co., Ltd.) as an alkali metal salt were dissolved in 10 mL of dimethylformamide, and the resulting solution was cast using an applicator and adjusted to a thickness of about 60 μm after drying. The cast polymer electrolyte solution was dried under reduced pressure at 100° C. for 24 hours to produce a polymer electrolyte membrane.

[0173] <Preparation of coin cells using polymer electrolyte membrane> (Example 26) The positive electrode used in Example 12, the polymer electrolyte prepared above, and the negative electrode used in Example 12 were laminated in this order, and rolled with a roll press to improve adhesion. Thereafter, the laminate was sealed, precharged, and then aged to prepare a coin-type lithium ion secondary battery.

[0174] Comparative Example 13 A polymer electrolyte membrane was prepared in the same manner as in Example 26 except that the compound 1-1 used in Example 26 was replaced with the compound 2-2, and a coin-type lithium ion secondary battery was prepared.

[0175] (Weight discharge capacity characteristics / high temperature cycle characteristics) The lithium ion secondary battery produced above was charged at 80°C with a constant current and constant voltage (cut at 0.01C) to 4.2V at a current equivalent to 0.05C, and then discharged to 3V at a constant current of 0.05C, which constitutes one cycle. The initial discharge capacity was calculated from the discharge capacity at the third cycle. The gravimetric discharge capacity characteristics were calculated using the following formula. ·Calculation formula for weight discharge capacity characteristics Weight discharge capacity characteristic (mAh / g) = Initial discharge capacity (mAh) / Weight of active material in the positive electrode mixture (g) The weight discharge capacity characteristics were ranked as follows: A:100mAh / g or more B: 90mAh / g or more and less than 100mAh / g C: 80mAh / g or more and less than 90mAh / g D: Less than 80mAh / g After that, the battery was cycled up to 10 cycles, and the capacity retention rate was calculated using the following formula. Capacity retention rate calculation formula Capacity retention rate (%) = Discharge capacity after 10 cycles (mAh) / Discharge capacity after 3 cycles (mAh) x 100 The capacity retention rate (high temperature cycle characteristics) was ranked as follows. A: 95% or more B: 90% or more but less than 95% C: 85% to less than 90% D: Less than 85% [Table 5]

Claims

1. At least one fluoropolyether represented by any one of the following formulas (1) to (3), and a salt. (1) R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2) R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3) R 3 -Rb 3 -O-Ra 3 -R 3 (In the formula, Ra 1 ~Ra 3 are each independently a polyoxyalkylene group containing 4 to 50 oxyalkylene units not containing fluorine, Ra 1 ~Ra 3 Each oxyalkylene unit is independently —CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 3 are each independently a fluoropolyether group represented by the following formula (4): R 1 and R 3 each independently represents a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 2 are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4)-Rf 1 -Rf-O-Rf 2 - (wherein, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

2. The Ra 1 ~Ra 3 The composition according to claim 1, wherein each of the groups is independently a polyoxyalkylene group represented by the following formula (Ra-I): (Ra-I): -(CH 2 CH 2 O)r(CH 2 CH(CH 3 )O)s(CH 2 CH(CH 2 CH 3 )O)t(CH 2 CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

3. The Ra 1 ~Ra 3 The composition according to claim 1 or 2, wherein the number average molecular weight of said compound is 40 to 4,000.

4. 3. The composition according to claim 1, wherein each Rf is independently a fluoropolyether group represented by the following formula (Rf-I): Formula (Rf-I): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 Rc 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer from 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeating unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e and f is 1 or more.

5. The composition according to claim 1 or 2, wherein each Rf is independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer from 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer from 1 to 200; the sum of c, d, e, and f is 2 or more; The order of the repeating units marked with c, d, e, or f is arbitrary.

6. The R 1 ~R 3 The composition according to claim 1 or 2, wherein each of the is independently a methyl group, an ethyl group, a trifluoromethyl group or a pentafluoroethyl group.

7. 3. The composition of claim 1, wherein the salt is a lithium salt.

8. 3. The composition according to claim 1, wherein the content of the salt is 0.1 to 30% by mass.

9. 3. The composition according to claim 1 or 2, which is liquid at any temperature between 25°C and 80°C.

10. The composition according to claim 1 or 2, wherein the content of the polyalkylene oxide represented by the following formula (5) is less than 20 mass %: (5)R 1B -(OCHR 1A (CH 2 )jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is 0 or an integer from 1 to 2; R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

11. An electrolyte comprising the composition of claim 1.

12. Ion conductivity is 1.0 x 10 -7 ~1.0 x 10 -3 12. The electrolyte according to claim 11, wherein the electrolytic solution has a viscosity of 1.0 S / cm.

13. The electrolyte according to claim 11 or 12, wherein the Li ion transport number is 0.2 to 0.

5.

14. A polymer electrolyte comprising the electrolytic solution according to claim 11.

15. An electrochemical device comprising the electrolyte solution according to claim 11 or 12 or the polymer electrolyte according to claim 14.

16. A fluoropolyether represented by the following formula (2A): (2A)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (In the formula, Ra 2 is a polyoxyalkylene containing 4 to 50 oxyalkylene units that are free of fluorine, Ra 2 Each oxyalkylene unit is independently —CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 2 are each independently a fluoropolyether group represented by the following formula (4A): R 2 are each independently a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms. (4A)-Rf 1 -Rf-O-Rf 2 - (wherein, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

17. The Ra 2 is a polyoxyalkylene group represented by the following formula (Ra-I): The fluoropolyether according to claim 16, wherein each Rf is independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): (Ra-I): -(CH 2 CH 2 O)r-(CH 2 CH(CH 3 )O)s-(CH 2 CH(CH 2 CH 3 )O)t-(CH 2 CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.) Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer from 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer from 1 to 200; the sum of c, d, e, and f is 2 or more; The order of the repeating units marked with c, d, e, or f is arbitrary.

Citation Information

Patent Citations

  • Nonaqueous fluoride salts, solutions, and their uses

    JP2018533156A

  • Liquid electrolytes for lithium batteries

    JP2019523529A

  • Silicon-based energy storage devices with fluorinated polymer containing electrolyte additives

    WO2019113526A1